Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.2166/ws.2004.0135
|View full text |Cite
|
Sign up to set email alerts
|

Particles in the drinking water system: from source to discolouration

Abstract: Water discolouration in networks results from increased turbidity due to high levels of suspended particles. Hydraulic incidents such as pipe burst or hydrant use impose extra shear stresses on sediment layers in the network, leading to particle resuspension. The mass balance over a network or parts of the network may be used to analyse the different sources and accumulation processes; this article focuses on the contribution of the “mass in” from the pumping station as particles. Three analysis methods have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Unwanted changes in microbial quality of drinking water can have adverse effects on distribution system and consumers. For example, during distribution, excessive growth of bacteria can lead to deterioration of drinking water quality in terms of safety (e.g., pathogens), consumer’s perception (e.g., discolouration) and operational aspects (e.g., biocorrosion; Szewzyk et al, 2000 ; Vreeburg et al, 2004 ; Sun et al, 2014 ). Changes in microbial water quality are a result of complex interactions between various organisms (bacteria, viruses, protozoa, higher organisms) regulated by: access to available growth-limiting nutrients, response to environmental conditions, such as water temperature, presence of potential residual disinfectant and other inhibitory substances, attachment of bacteria to pipe walls, particle deposition, sediment re-suspension and biofilm formation.…”
Section: Introductionmentioning
confidence: 99%
“…Unwanted changes in microbial quality of drinking water can have adverse effects on distribution system and consumers. For example, during distribution, excessive growth of bacteria can lead to deterioration of drinking water quality in terms of safety (e.g., pathogens), consumer’s perception (e.g., discolouration) and operational aspects (e.g., biocorrosion; Szewzyk et al, 2000 ; Vreeburg et al, 2004 ; Sun et al, 2014 ). Changes in microbial water quality are a result of complex interactions between various organisms (bacteria, viruses, protozoa, higher organisms) regulated by: access to available growth-limiting nutrients, response to environmental conditions, such as water temperature, presence of potential residual disinfectant and other inhibitory substances, attachment of bacteria to pipe walls, particle deposition, sediment re-suspension and biofilm formation.…”
Section: Introductionmentioning
confidence: 99%
“…Water quality changes are usually attributed to microbial processes in distribution pipelines, including growth of benign autochthonous bacteria and/or re-suspension or detachment of bacterial cells from pipe wall sediments and/or biofilms into the bulk water. Though the involved organisms are not necessarily hygienically relevant, water quality deterioration is of concern for water utilities, as it is a major cause of customer complaints and maintenance costs [1,2]. Numerous studies have shown that drinking water distribution networks are dynamic systems in which spatial and temporal changes take place in the autochthonous microbial community, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Under normal operating conditions, these deposits are attached to parts of the distribution system where the hydraulic conditions are favorable. Under high-flow conditions, however, the resulting high velocity can disturb the deposited materials, inducing aesthetic and/or microbial problems by the suspension of particles of the deposits in drinking water [9][10][11][12]. The effects of localized high demand on turbidity and particle counts can be significant for the intermittent water replenishment of large-demand customers.…”
Section: Introductionmentioning
confidence: 99%